Advanced Composites and Applications: Book of Abstracts,﻿ February 11th, 2025 - 83rd Scientific conference of the University of Latvia (University of Latvia, 2025)
Traditionally, the "Advanced Composites and Applications" session will be organized by the Institute for Mechanics of Materials of the University of Latvia (LU MMI) on 11.02.2025 as part of the annual 83rd scientific conference of the University of Latvia. It was organized remotely in Zoom. The official language of the section was English. The duration of the presentation was 10 minutes. The section will be devoted to the discussion of the recent results within the following topics: -structure and properties of polymers and polymer-based composites; -long-term properties, creep, and environmental ageing; -composites for advanced applications; -mechanical aspects of technology; -multifunctional properties.
Keywords: structure and properties of polymers and polymer-based composites; composites for advanced applications; long-term properties; creep; environmental ageing; smart materials and applications; Research Subject Categories::NATURAL SCIENCES::Physics